The effect of SiC and Y2O3 inclusion on microstructure and mechanical properties of Al 5052 composite fabricated through Friction Stir Process - Panneerselvam Natarajan; T. Sekar; Venkatesh Chenrayan; L. Rajeshkumar (Heliyon)
A consistent research attempt to develop newer lightweight-high strength materials facilitates the automobile sector to excel in product efficiency. The present research is another endeavour to anchor the automobile industries by exploring novel composite. The different earth elements SiC and Y2O3 are utilised for the hybrid reinforcement of Al 5052 alloy in four different weight proportions. Friction Stir Processing (FSP) is employed to fabricate composites. The microstructure analysis conducted through the optical microscope reveals the formation of fine grain size at the nugget zone. The effect of dynamic recrystallization and particulate strengthening is reflected in the inflated tensile strength of Al-3SiC-1Yo. The microhardness test results manifest the higher hardness at the nugget zone and descending to the Heat Affected Zone (HAZ) through the Thermo Mechanically affected zone (TMAZ). The post-tensile fracture morphological observation through Scanning Electron Microscopy (SEM) explores the particulate strengthening mechanisms offered by the piled-up dislocation densities. The hybrid hard particle inclusion in the matrix helps to achieve 63.87 %, 50 % and 35 % improvement in tensile strength, hardness and impact toughness of SiC and Y2O3 reinforced FSPed Al alloy. Further, a higher level of inclusion of Y2O3 beyond 0.5 % is found to dent the properties due to the agglomeration effect of Y2O3 particles.